The use of the irish electoral register for population estimation - Whelan, BJ; Keogh, G (Economic & Social Studies, 1980)
A strong relationship is shown to exist between the number of registered electors in a county and the county's population in census years. This relationship can be used to estimate county populations in intercensal years. Total population estimates for the years 1961 to 1979 are derived and are used to construct a net migration series for the same period. This series is compared with migration series implicit in the Central Statistics Office intercensal population series.
Keywords: Ireland; Demographics